Dairy Free - Regan, Lisa; Stimpson, Jo (Sywell, igloobooks, 2017)
Dairy Free features mouth-watering recipes, all free from dairy products for those with intolerances or aversions to dairy
"Ditch the dairy and feel nourished"--Cover.
Keywords: Milk-free diet -- Recipes; Cookbooks